Literature as Testimony: The Poetics of Memory in Poetry - Rogova Gaxha, Blerina (Primerjalna književnost, 2022)
This article examines the representation, transmission, and circulation of war memory, and the role of personal and collective memory in shaping meanings, attitudes, and identities. The discussion will alternate between two aspects of the topic: the particular claim to truth that witness literature puts forward, and the process that leads from catastrophe to creativity, turning the victim into a writing witness who can undo forgetting and denial. War memory and its intersection with the concept of trauma is explored in the works of authors Xhevdet Bajraj and Ivana Bodrožić, renowned poets of contemporary literature in their respective countries. Their views provide a geopoetic and cultural background for a theoretical discussion of literary and cultural aspects of war memory. The main objective is to examine the concept of poetry as testimony and its relevance to contemporary literature in Croatia and Kosovo. The theorizing introduction is followed by poems by authors, but at the end there is a theoretical offshoot on the topic.